2014
DOI: 10.1167/iovs.14-14417
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of MMP14 in MMP2 processing and recruitment in exosomes of corneal fibroblasts

Abstract: PURPOSE. Matrix metalloproteinase (MMP) 14 has been shown to promote angiogenesis, but the underlying mechanisms are poorly understood. In this study, we investigated exosomal transport of MMP14 and its target, MMP2, from corneal fibroblasts to vascular endothelial cells as a possible mechanism governing MMP14 activity in corneal angiogenesis. METHODS.We isolated MMP14-containing exosomes from corneal fibroblasts by sucrose density gradient and evaluated exosome content and purity by Western blot analysis. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 42 publications
(53 reference statements)
1
62
0
Order By: Relevance
“…A large number of MMPs, ADAMs and ADAMTSs have been identified on exosomes and have been shown to be catalytically active (Shimoda and Khokha, 2013). Thus far in the eye, only two studies have identified MMPs as exosomal proteins, MMP-14 with corneal fibroblast exosomes (Han et al, 2015) and MMP-2 with trabecular meshwork exosomes (Stamer et al, 2011). …”
Section: Exosomes and Extracellular Matrix (Ecm)mentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of MMPs, ADAMs and ADAMTSs have been identified on exosomes and have been shown to be catalytically active (Shimoda and Khokha, 2013). Thus far in the eye, only two studies have identified MMPs as exosomal proteins, MMP-14 with corneal fibroblast exosomes (Han et al, 2015) and MMP-2 with trabecular meshwork exosomes (Stamer et al, 2011). …”
Section: Exosomes and Extracellular Matrix (Ecm)mentioning
confidence: 99%
“…A critical component throughout this process is the transmembrane matrix metalloproteinase-14 (MMP-14). Corneal fibroblasts release exosomes with MMP-14, which are taken up by endothelial cells (Han et al, 2015). Exosomal MMP-14 activity is critical for the accumulation and activation of MMP-2 in the exosomes (Han et al, 2015).…”
Section: Exosomes In Ocular Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The exact role of exosomes in cell-matrix interactions and degradation is unclear; however exosomes from a number of sources have been shown to possess proteolytic activity crucial in degrading the ECM. The membrane bound MT1-MMP has been detected on exosomes [45] and was able to cleave collagen 1, gelatin and pro-MMP2 into its active form [46]. MMP activity is critically important for maintaining outflow facility and therefore TM function [11].…”
Section: Fig 4 Molecular Interaction Between Fibronectin and Heparanmentioning
confidence: 99%
“…Moreover, the amount of secreted microvesicles has also been correlated with the expression of phosphorylated protein kinase B (Ak) t and extracellular signal-regulated protein kinases (ERKs) which are crucial elements regulating apoptosis and cell differentiation processes. The microvesicles have also been shown to be enriched for multiple proteolytic enzymes, like MMP-2 and MMP-14 [12,13]. Though these enzymes are important for various cellular processes, they could also impact the quality and quantity of the product in culture.…”
Section: Introductionmentioning
confidence: 99%